2005
DOI: 10.1111/j.1538-7836.2005.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and propagation of coagulation from tissue factor‐bearing cell monolayers to plasma: initiator cells do not regulate spatial growth rate

Abstract: To cite this article: Ovanesov MV, Ananyeva NM, Panteleev MA, Ataullakhanov FI, Saenko EL. Initiation and propagation of coagulation from tissue factor-bearing cell monolayers to plasma: initiator cells do not regulate spatial growth rate. J Thromb Haemost 2005; 3: 321-31.Summary. Exposure of tissue factor (TF)-bearing cells to blood is the initial event in coagulation and intravascular thrombus formation. However, the mechanisms which determine thrombus growth remain poorly understood. To explore whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
1
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 35 publications
6
92
1
7
Order By: Relevance
“…To quantitatively characterize the spatial clotting process we calculated the size of the clot as a function of time from the light scattering profiles. We assumed that the clot size at a given time, Size(t), was equal to the distance from the activator to the point where fibrin concentration (proportional to the light scattering intensity [8]) declined to 50% of the plateau value ( fig. 2 С-D).…”
Section: Materials and Methods Of Experimental Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantitatively characterize the spatial clotting process we calculated the size of the clot as a function of time from the light scattering profiles. We assumed that the clot size at a given time, Size(t), was equal to the distance from the activator to the point where fibrin concentration (proportional to the light scattering intensity [8]) declined to 50% of the plateau value ( fig. 2 С-D).…”
Section: Materials and Methods Of Experimental Investigationmentioning
confidence: 99%
“…It is shown that clotting under these experimental conditions is sensitive to congenital deficiencies of FVIII, FIX [6,7] and FXI [3,8], that are associated with abnormal clotting commonly referred as haemophilias A, B and C, respectively. Extremely low concentrations of FVIII, FIX and, to a lesser extent, FXI have been shown to disrupt clot propagation in space.…”
Section: Introductionmentioning
confidence: 99%
“…68 These findings suggest that thrombin generated on the surface of platelets during the propagation phase dictates that rate of fibrin clot formation away from the initiating cells. [67][68][69][70] Fibrin formation during cell-mediated thrombin generation likely includes a complex spatial component as well. It is likely that this physical progression of procoagulant activity from the tissue factor-bearing cell (low levels of thrombin generation) to the activated platelet surface (rapid burst of thrombin generation) induces the formation of a thrombin gradient in space.…”
Section: Effect Of the Thrombin Generation Pattern And Location On Fimentioning
confidence: 99%
“…Since different tissue factor-bearing cells support different levels of procoagulant activity, they differ in their ability to initiate fibrin formation. 68,71-73 Interestingly, Ovanesov et al (2005) showed that the rate of thrombin generation on tissue factor-bearing cells does not influence the rate of propagation of fibrin into the plasma milieu. 68 Rather, propagation of fibrin away from the site of initiation depends on the plasma composition and procoagulant activity of the surrounding milieu.…”
mentioning
confidence: 99%
“…The observation that information on clot properties provides better guidance for preventing bleeding and the effectiveness of treatment than clotting time Introduction to haemostasis from a pharmacodynamic perspective Br J Clin Pharmacol / 72:4 / 541 in critically ill patients with bleeding problems [44,45] may be considered a first step in this direction.This can be taken further when evaluations will also be done that study clot growth/propagation in conditions with flow/circulation because this clinically relevant condition is not mimicked in current in vitro tests [46,47].…”
Section: Phenotypementioning
confidence: 99%